The impact of the Hanni and Mumford model on providing students of the Institute of Fine Arts with composition skills in Fatimid calligraphy (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of the Hani and Mumford model to provide students of the Institute of Fine Arts with composition skills in Fatimid calligraphy). To achieve the goal of the research, the researcher formulated the two null hypotheses, which are as follows:1_There are no statistically significant differences at the level of significance (0.05) between the average scores of the experimental group students and the control group students in the cognitive achievement test for the Arabic (Fatimi) calligraphy subject2_There are no statistically significant differences at the level of significance (0.05) between the average scores of the students in the experimental group and the students in the control group in the post-test of skill performance of the Arabic (Fatimi) calligraphy subject.The current research community consisted of students from the Institute of Fine Arts, Department of Arabic Calligraphy and Ornamentation (second year), morning study, in Baghdad Governorate, for the academic year (2023 - 2024 AD), who are studying Arabic calligraphy, and the size of the community reached (279). student, and the researcher took a research sample of (54) students. The researcher chose the sample intentionally, and the researcher constructed a cognitive achievement test, and a test for skill performance in the Fatimid Kufic script subject.